2012
DOI: 10.1002/chir.22072
|View full text |Cite
|
Sign up to set email alerts
|

The Stereoselective Sulfate Conjugation of 4′‐Methoxyfenoterol Stereoisomers by Sulfotransferase Enzymes

Abstract: The presystemic sulfate conjugation of the stereoisomers of 4-methoxyfenoterol, (R,R)-MF, (S,S)-MF, (R,S)-MF, and (S,R)-MF, was investigated using commercially available human intestinal S9 fractions, a mixture of sulfotransferase (SULT) enzymes. The results indicate that the sulfation was stereospecific and that an S-configuration at the β-OH carbon of the MF molecule enhanced the maximal formation rates with (S,R)-MF > (S,S)-MF > (R,S)-MF ≈ (R,R)-MF, and competition studies demonstrated that (S,R)-MF is an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Second, the docking results were also investigated based on three-dimensional pharmacophore features such as hydrogen bonds, hydrophobic contacts, or aromatic areas. To the best of our knowledge, this approach has rarely been applied to SULT docking studies because primarily hydrogen bonds have been considered to evaluate docked ligand conformations (26,(67)(68)(69). Due to the nature of the active site of SULT1E1 (a barrel-like structure lined with lipophilic and/or aromatic amino acids), the consideration of hydrophobic areas and aromatic contacts bears advantages as shown by the predictive power of the presented in silico model for ligands of SULT1E1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the docking results were also investigated based on three-dimensional pharmacophore features such as hydrogen bonds, hydrophobic contacts, or aromatic areas. To the best of our knowledge, this approach has rarely been applied to SULT docking studies because primarily hydrogen bonds have been considered to evaluate docked ligand conformations (26,(67)(68)(69). Due to the nature of the active site of SULT1E1 (a barrel-like structure lined with lipophilic and/or aromatic amino acids), the consideration of hydrophobic areas and aromatic contacts bears advantages as shown by the predictive power of the presented in silico model for ligands of SULT1E1.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the enzyme structure, computational studies have investigated the mechanism of inhibition of SULT1E1 by nucleotides (25) and stereoselectivity of sulfonation via docking (26), analyzed the sulfonation reaction using QM/MM methods (27), and utilized molecular docking to predict ligand binding (28). Here, we report on a novel approach of computer-based metabolism prediction for human SULT1E1.…”
mentioning
confidence: 99%
“…Conformations with highest binding energies were selected for QM/MM calculations (at B3LYP/6-311 + G(d,p)//AMBER level) for estimating the reaction barriers. Distances between catechol oxygen atoms to be methylated and sulfur atom of S-adenosyl-L-methionine (2.95 −3.10 Å) and the O C S angle (160)(161)(162)(163)(164)(165)(166)(167)(168)(169)(170) were constrained for selection of starting geometries form the MD trajectories.…”
Section: Simulations To Understand Regioselectivity In Comt-mediated Methylationsmentioning
confidence: 99%
“…Iyer et al worked on the regioselective and stereospecific phenolic sulfonation of 4′‐methoxyfenoterol (MF), a potential candidate for the treatment of congestive heart failure . Experimental results showed that sulfonation of MF is stereoselective.…”
Section: Prediction Of Phase II (Ugt and Non‐ugt) Drug Metabolismmentioning
confidence: 99%